Finite element analysis of heat transfer behavior in glass fiber/metal composite materials under constant heat load - Wang Ke; Zhu Ting; Ma Qian; Wang Shudong; Zhou Hongtao; Zhao Jumei; Jin Limin (AUTEX Research Journal)
A finite element analysis model was employed to analyze the heat conduction behavior of glass fiber/metal (stainless steel, aluminum, or oxygen-free copper) composite materials under a constant thermal load of 100°C on the metal surface, i.e., the temperature distribution after reaching thermal equilibrium. By comparing and analyzing the effects of different metal materials, different air convection heat transfer capabilities, and different metal phase thicknesses, the heat transfer mechanism is elaborated. The results indicate that the metal with stronger heat conduction capacity induces more uniform temperature distribution, while the temperature uniformity on the fiber is relatively worse. Besides, with the increase of the air convection heat transfer coefficient, the temperature on the fiber phase shows a significant downward trend, however, the impact on the metal phase remains limited. In addition, the metal thickness primarily affects the weight or rigidity of the composite material, with minimal impact on temperature distribution.